THERAPEUTIC PEDAGOGY IN NEUROLOGICAL AND MENTAL DISEASES OF CHILDREN (Pedagogy of Higher and Secondary Education, 2008)
In this article are risen the questions of the therapeutic pedagogy for the pupils with limited possibilities and suffering from nervous and mentally diseases.